(untitled) (Biological Sciences - PJSIR, 2005)
This work reports the influence of local clay, charcoal, silica-sand, limestone and carbon black on the crosslink density, hardness, resilience and hysteresis of the natural rubber compound. The results revealed that all the fillers enhanced the crosslink density and hardness of the gum stock. Charcoal showed higher values of crosslink density, hardness and hysteresis than the other local fillers. At relatively low loading, local fillers showed appreciably higher resilience and slightly lower hysteresis than carbon black charcoal, being the least resilient and most hysteric. The present work suggests that the denser is the crosslink of the composite, the harder, less resilient and the more hysteric the composite becomes.